Recognition of DNA bulges by dinuclear iron(II) metallosupramolecular helicates - Malina, Jaroslav; Hannon, Michael J; Brabec, Viktor (The FEBS journal, 2014)
Bulged DNA structures are of general biological significance because of their important roles in a number of biochemical processes. Compounds capable of targeting bulged DNA sequences can be used as probes for studying their role in nucleic acid function, or could even have significant therapeutic potential. The interaction of [Fe(2)L(3)](4+) metallosupramolecular helicates (L = C(25)H(20)N(4)) with DNA duplexes containing bulges has been studied by measurement of the DNA melting temperature and gel electrophoresis. This study was aimed at exploring binding affinities of the helicates for DNA bulges of various sizes and nucleotide sequences. The studies reported herein reveal that both enantiomers of [Fe(2)L(3)](4+) bind to DNA bulges containing at least two unpaired nucleotides. In addition, these helicates show considerably enhanced affinity for duplexes containing unpaired pyrimidines in the bulge and/or pyrimidines flanking the bulge on both sides. We suggest that the bulge creates the structural motif, such as the triangular prismatic pocket formed by the unpaired bulge bases, to accommodate the [Fe(2)L(3)](4+) helicate molecule, and is probably responsible for the affinity for duplexes with a varying number of bulge bases. Our results reveal that DNA bulges represent another example of unusual DNA structures recognized by dinuclear iron(II) ([Fe(2)L(3)](4+)) supramolecular helicates.
Keywords: retardační test; konformace nukleové kyseliny; DNA; železnaté sloučeniny; denaturace nukleových kyselin; Ferrous Compounds; Nucleic Acid Denaturation; Electrophoretic Mobility Shift Assay; Nucleic Acid Conformation